Sistem Informasi Pendaftaran Member Berbasis Web Pada Meadow Terrace Sports Club - Asyharudin; Hylenarti Hertyana (Ladang Artikel Ilmu Komputer, 2023)
Information technology is developing fast, almost every organization and company has used technology in its operational implementation so that information technology is an integral part of supporting the success of an organization and company. Meadow Terrace Sports Club is a fitness center that has various facilities for visitors such as a standard athletic swimming pool, SPA & Sauna, basketball courts, tennis courts and quality fitness equipment. Meadow Terrace Sports Club, which is located in Housing The Green BSD City, Serpong, already has more than 400 active members. In addition to serving visitors who are already registered as members, Meadow Terrace Sports Club also serves visit transactions for the public who are not yet members with more than one visit. than 50 people per day. Data management at Meadow Terrace Sports Club is still carried out using manual and conventional methods using spreadsheet or excel applications so that it takes a long time to do each job to support business processes. In order to realize good information technology governance in order to create productivity and quality as well as good financial conditions and to avoid failures or errors, as well as to help Meadow Terrace Sports Club management more easily manage member data and be more efficient in preparing reports, it is necessary to have one system that can accommodate these needs.